Relasi Sunni-Syi’ah dalam Budaya Politik Sektarian dan Pengaruhnya Terhadap Pemerintahan Lebanon - Mukhsinin, Nasrul; Rofii, Muhammad Syaroni; al-Asyurra, Khairil Zaki (Journal Of Middle East and Islamic Studies, 2022)
In a national pact, the Maronite Christians share power with Sunni Muslims. The agreement changed to the Ta'if agreement by adding Shia Muslims in the government. The growing influence of Shia politics along with the weakening of Maronite Christian influence made the axis of sect competition focused on Sunni and Shia groups. After the assassination of Prime Minister Rafiq Hariri, both of them played a political role in dividing political factions in the state government. Sunni-Shi'a political relations are very influential on the course of the Lebanese confessional government. This is a challenge for Hassan Diab as the new Prime Minister of Lebanon. Although he is a Sunni Muslim, his government is seen as a coalition of Hezbollah, leading the Sunni-led March 14 alliance to withdraw from government. Keywords:Sunni, Syiah, Government, Lebanon, Politic